2013
DOI: 10.1111/acer.12084
|View full text |Cite
|
Sign up to set email alerts
|

Brand-Specific Consumption of Alcohol Among Underage Youth in the United States

Abstract: Background Little is known about brand-specific alcohol consumption among underage youth, as existing information is collected at the level of alcoholic beverage type. This study identifies the alcohol brands consumed by a nationally representative sample of underage youth in the U.S. Methods We obtained a national sample of 1,032 underage youth, ages 13–20, using a pre-recruited internet panel maintained by Knowledge Networks. Youth ages 18–20 were recruited directly from the panel via email invitation. Tee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 34 publications
0
103
0
Order By: Relevance
“…Based on previous research demonstrating brands of alcohol reported as favored and popular among underage drinkers (Siegel, DeJong, et al, 2013;Tanski et al, 2011), as well as those appearing in popular music (Siegel, Johnson, et al, 2013), we chose 8 search strings reflecting a variety of brands across several types of alcoholic beverages. The brands were -Bud Light‖ (beer), -Coors Light‖ (beer), -Grey Goose‖ (vodka), -Hennessey‖ (cognac), -Jack Daniel's‖ (whiskey), -Mike's Hard‖ Lemonade (flavored alcohol drink), -Patron‖ (tequila), and -Smirnoff‖ (flavored alcohol and also vodka).…”
Section: Search Algorithm and Quality Controlmentioning
confidence: 99%
“…Based on previous research demonstrating brands of alcohol reported as favored and popular among underage drinkers (Siegel, DeJong, et al, 2013;Tanski et al, 2011), as well as those appearing in popular music (Siegel, Johnson, et al, 2013), we chose 8 search strings reflecting a variety of brands across several types of alcoholic beverages. The brands were -Bud Light‖ (beer), -Coors Light‖ (beer), -Grey Goose‖ (vodka), -Hennessey‖ (cognac), -Jack Daniel's‖ (whiskey), -Mike's Hard‖ Lemonade (flavored alcohol drink), -Patron‖ (tequila), and -Smirnoff‖ (flavored alcohol and also vodka).…”
Section: Search Algorithm and Quality Controlmentioning
confidence: 99%
“…34 To assess the impact of these agreements on activity on alcoholbranded SNS, and as a substantial improvement over earlier methodologies, we licensed the CrowdTangle Discovery App (Crowdtangle, Inc., Baltimore, MD, USA) that automates monitoring of Facebook activity. Following 15 brands found most popular among US young people (ages 13-20) in a recent national survey, 35 CrowdTangle permitted us to track and measure both brand activity in terms of posts to their pages, and user engagement in the forms of posting, liking, and sharing done by users of these brand pages. Posting means a brand or user has added an original piece of content directly to the brand's page, such as a comment, photo, or a video.…”
Section: Internet Audience Measurement and The Growth Of Social Mediamentioning
confidence: 99%
“…Youth consumption of flavored-alcoholic beverages: brand-specific research An internet-based survey was conducted to assess the consumption of 898 brands of alcoholic beverages -including 62 brands of FABs -among over 1000 drinkers aged 13-20. The findings indicate that in 2012, FABs ranked as the second leading alcoholic beverage type consumed, accounting for over 16% of the alcohol consumption market share (19). Nearly half of youth drinkers reported consuming FABs in the past 30 days and four of the leading 25 brands consumed were FABs, including Four Loko (9,19).…”
Section: Introductionmentioning
confidence: 98%
“…Nearly half of youth drinkers reported consuming FABs in the past 30 days and four of the leading 25 brands consumed were FABs, including Four Loko (9,19).…”
Section: Introductionmentioning
confidence: 99%